1979
DOI: 10.1203/00006450-197907000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Postantal Development of Renin-Angiotensin-Aldosterone System, RAAS, in Relation to Electrolyte Balance in Premature Infants

Abstract: Summarycharacteristic for hypoaldosteronism, it is tempting to postulate a causal relationship between physiologic hyponatremia and the In an attempt to provide information about the role of RAAS in function of renin-angiotensin-aldoster~ne system (RAAS) in low development of late hyponatremia in low-birthweight neonates, birthweight neonate.simultaneous measurement of plasma renin activity, (PRA),In an attempt to obtain information about the role of RAAS in plasma aldosterone concentration (PA), and urinary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
1
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(11 citation statements)
references
References 15 publications
1
8
1
1
Order By: Relevance
“…It has been shown that the renin-angiotensin-aldosterone system is highly active during the neonatal period, particularly in premature infants (l9,20). Our data on high aldosterone levels in SGA infants also suggest an activation of this system, whereas in two other studies (7,8), limited to the 2nd day, and to the 7th day of life, respectively, no difference was found between SGA and AGA infants. Sulyok et al (8), however, described a tendency to higher plasma renin activity and urinary aldosterone excretion in intrauterine growth-retarded neonates.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…It has been shown that the renin-angiotensin-aldosterone system is highly active during the neonatal period, particularly in premature infants (l9,20). Our data on high aldosterone levels in SGA infants also suggest an activation of this system, whereas in two other studies (7,8), limited to the 2nd day, and to the 7th day of life, respectively, no difference was found between SGA and AGA infants. Sulyok et al (8), however, described a tendency to higher plasma renin activity and urinary aldosterone excretion in intrauterine growth-retarded neonates.…”
Section: Discussioncontrasting
confidence: 50%
“…Only few and contradictory results on corticosteroid levels in SGA infants have been reported (4)(5)(6), partly combining data from infants born by various modes of delivery, or infants at various postnatal and gestational ages. Because of the amount of blood necessary for the determination of corticosteroids, these studies were limited to single steroids such as cortisol (5) or aldosterone (7,8). For the same reason, longitudinal studies throughout the early neonatal period are not available.…”
mentioning
confidence: 99%
“…This suggests that the inability to retain a normal percentage of the dietary salt intake is somehow related to the level of immaturity of the kidney. One suggestion has been that the immature kidney is relatively insensitive to the sodium-retaining effect of the endogenous aldosterone (4). However, it has been shown that one feature of the defect is that a larger than normal percentage of the renal filtrate is delivered to the distal tubule, suggesting that too little filtrate is reabsorbed in the proximal tubule (2).…”
mentioning
confidence: 99%
“…Only a slight increase in the plasma K+ level independently promoted aldosterone secretion in a K+-loading study of adults (6). No associations between spot plasma K+ levels and urinary or plasma aldosterone levels have been reported in infants (14,15,16,17). However, from these results, it is not clear whether normokalemia suppressed the plasma aldosterone or hypoaldosteronism caused the hyperkalemia.…”
Section: Discussionmentioning
confidence: 94%